Hypoplastic left heart syndrome secondary to intrauterine rhabdomyoma necessitating single ventricle palliation - Arshid Mir; Catherine Minor Ikemba; Surendranath R Veeram Reddy (Wolters Kluwer Medknow Publications, 2014)
Rhabdomyoma, a benign hamartomatous tumor of the cardiac embryonic myocyte, is the most common intrauterine cardiac tumor and accounts for 0.12% of prenatal fetal studies. Fetal cardiac rhabdomyomas increase in size during second and early third trimester and spontaneously regress postnatally. The clinical presentation is usually benign, however, compromise of the ventricular outflow tract leading to decreased cardiac output and fetal death have been reported. We present a case of large cardiac rhabdomyoma in a fetus that might have caused complete left ventricular outflow tract obstruction and development of hypoplastic left heart syndrome (HLHS) necessitating postnatal single ventricle palliation therapy. The clinical course and outcomes of prenatally diagnosed cardiac rhabdomyoma are reviewed and theories of the development of hypoplastic left heart syndrome are explored.